Let $f \in C[a,b]$ with $$\int_{a}^{b}f(x)x^{n}dx=0$$ for all $n\in \mathbb{N}$. Prove $f=0$.

I got the intuition to prove this with induction over $n \in \mathbb{N}$, for $n=0$, I have $\int_{a}^{b}f(x)dx=0$. So how I got that $f=0$? Also, how I end up the proof? Any help will be appreciated. Thanks

  • 2
    $\begingroup$ Induction isn't the right approach here, I'm afraid. $\endgroup$ – Jakobian Feb 27 at 1:33
  • $\begingroup$ Any other idea? @Jakobian $\endgroup$ – Cos Feb 27 at 1:36
  • $\begingroup$ A quite similar question was asked about a day ago at Use Weierstrass to show $f(x)=0$. It asks a question of the same form as yours, except it's restricted to $a = 0$, $b = 1$, and $n$ being even. Nonetheless, you may find the answers there helpful to you. $\endgroup$ – John Omielan Feb 27 at 1:36

Based on the context set in the text of the question, I assume we can take

$0 \in \Bbb N; \tag 1$

I also take it that

$a \le b. \tag 2$

We have the following

Lemma: Suppose

$g_n \in C[a, b] \tag 3$

is a sequence such that

$g_n \to f \; \text{as} \; n \to \infty \tag 4$


$\displaystyle \lim_{n \to \infty} \int_a^b fg_n \; dx = \int_a^b f^2 \; dx. \tag 5$

Proof of Lemma:

Observe that

$\displaystyle \int_a^b f^2 \; dx - \int_a^b f g_n \; dx = \int_a^b (f^2 - fg_n) \; dx = \int_a^b f(f - g_n) \; dx; \tag 7$


$\left \vert \displaystyle \int_a^b f^2 \; dx - \int_a^b f g_n \; dx \right \vert = \left \vert \displaystyle \int_a^b f(f - g_n) \; dx \right \vert$ $\le \displaystyle \int_a^b \vert f (f - g_n) \vert \; dx = \displaystyle \int_a^b \vert f \vert \vert f - g_n \vert \; dx \le \int_a^b \vert f \vert \Vert f - g_n \Vert \; dx = \Vert f - g_n \Vert \int_a^b \vert f \vert \; dx; \tag 8$

passing to the limit,

$\lim_{n \to \infty} \left \vert \displaystyle \int_a^b f^2 \; dx - \int_a^b f g_n \; dx \right \vert \le \lim_{n \to \infty} \Vert f - g_n \Vert \displaystyle \int_a^b \vert f \vert \; dx = 0; \tag 9$

thus (5) binds. End: Proof of Lemma.

With this lemma in hand we proceed with the observation that the function

$x:[a, b] \to \Bbb R \tag{10}$

separates points in $[a, b]$; that is, for any

$c_1, c_2 \in [a, b], \; c_1 \ne c_2, \tag{11}$

we have

$x(c_1) = c_1 \ne c_2 = x(c_2); \tag{12}$

it then follows from the Stone-Weierstrass theoremthat the sub-algebra of $C[a, b]$ generated by $x$ and the constant functions is dense; since this sub-algebra is the set of real polynomials in $x$, it follows that there exists a sequence of polynomials $p_n(x)$ such that

$p_n(x) \to f(x) \; \text{in} \; C[a, b]; \tag{13}$

that is,

$\displaystyle \lim_{n \to \infty} \Vert p_n(x) - f(x) \Vert = 0, \tag{14}$

and from the hypothesis that

$\displaystyle \int_a^b x^m f(x) \; dx = 0, \; \forall m \in \Bbb N, \tag{15}$

the linearity of the integral allows us to conclude that

$\displaystyle \int_a^b p_n(x) f(x) \; dx = 0, \forall n \in \Bbb N; \tag{16}$

now applying the lemma we find

$\left \vert \displaystyle \int_a^b f^2(x) \; dx \right \vert = \lim_{n \to \infty} \left \vert \displaystyle \int_a^b f^2 \; dx - \underbrace{\int_a^b p_n f \; dx}_{0} \right \vert \le \lim_{n \to \infty} \Vert f - p_n \Vert \displaystyle \int_a^b \vert f \vert \; dx = 0, \tag{17}$

which forces

$\displaystyle \int_a^b f^2(x) \; dx = 0; \tag{18}$

now since $f^2(x)$ is a non-negative continuous function it follows that

$f(x) = 0, \forall x \in [a, b]. \tag{19}$



Use the fact that polynomials are dense in $C[a,b]$ with the supremum norm (see the Stone–Weierstrass theorem).

Due to the linearity of integration, your assumption implies that

$$\int_a^b f(x)P(x) \mathrm{d}x = 0 \hspace{10px}(\star)$$

for any polynomial $P(x)$.

By the Stone-Weierstrass theorem, you can find a sequence of polynomials $\{P_n\}_{n=1}^{\infty}$ such that $\lim_{n\to\infty}P_n(x) = f(x)$ uniformly. Since the convergence is uniform, we can exchange limit and integration operators. Therefore, we have

$$\lim_{n\to\infty}\underbrace{\int_a^b f(x)P_n(x)\mathrm{d}x}_{\text{this is zero by }(\star)} = \int_a^bf(x)\lim_{n\to\infty}P_n(x)\mathrm{d}x= \int_a^b f(x)^2 \mathrm{d}x = 0$$

Since $f^2(x) \geq 0$, we conclude that $f=0$ on $[a,b]$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.